0749 Case Simulations in Obstructive Sleep Apnea and Narcolepsy: Patients That Keep You Up at Night. (27th May 2020) - Bogan, R K; Rorie, K; Faler, W E; Gross, T; Perez, J; Tordoff, S A; Salinas, G
Abstract: Introduction: 3 CME interventions used online case simulations to facilitate the recognition of residual EDS in patients with narcolepsy and OSA and to improve decision-making when developing strategies for long-term management of residual EDS. Methods: Outcomes data were obtained from 3, 30-minute case simulations on residual EDS. Surveys assessing knowledge, confidence, and behavior were administered pre- and post-activity. A separate evaluation provided demographics and other variables used in the model. Data from a 2-month follow-up survey were analyzed to determine performance effects on the learner population (n = 30) compared to matched controls (n = 30). Statistical comparisons of data from baseline to post-intervention were made using McNemar's tests and paired t-tests. Additionally, predictive modeling was applied to evaluate variables predictive of evidence-based decisions. A longitudinal analysis of results was conducted to evaluate knowledge and performance changes in sleep-related initiatives between 2016 - 2019. Results: Learners outperformed controls in utilizing the Epworth Sleepiness Scale (ESS) and are more likely to interpret ESS scores to confirm EDS diagnosis and select appropriate treatment options in managing patients with EDS. Further, learners are more likely than controls to engage in shared decision-making with patients. When given a real-world case, learners are more likely than controls to identify symptoms and order correct tests. Learners were also more likely to select best treatment options for the patient more often than non-learners. Continued education needs to focus on treatment options for patients with narcolepsy. Conclusion: Follow-up assessments were conducted to understand lasting performance in learners attributable to this education. Using data from learners compared to matched controls, we found the education had an effect size of 23% (Cohen's d = 0.33). This indicates that for every 100 clinicians exposed to this education, 23 will perform more according to evidence than if they were not exposed. Support: The educational activity described in this abstract was supported by an educational grant from Jazz Pharmaceuticals, Inc.